Land capitalization model for sustainable tourism based on PLS-SEM - Sukriah Erry (E3S Web of Conferences)
Tourism development faces problems related to land capitalization. Without an adequate solution, this problem threatens sustainable tourism development strategies in Indonesia. This research aims to develop a land capitalization model for tourism development in Lembang, West Java. This model was prepared using the Partial Least Squares and Structural Equation Modeling (PLS-SEM) method involving various physical, environmental, and socio-economic factors. This research shows that the capitalization model could describe actual conditions, although the relationship between latent variables was weak. There are three patterns of land capitalization for tourism, where investors 1) invest in land and immediately convert it into a tourism business, then the prices increase sharply, 2) invest in land and then change the use into a tourism business accompanied by control of the surrounding and then the price increases, and 3) invest gradually with acquiring land until they create exclusive areas and increase the price. To control land capitalization in tourism areas, land ownership regulations are needed to protect ownership for local communities.